A change in university lecturers’ perception of e-learning tools for instructional delivery at Midlands State University: from techno-phobic to technology savvies - Chitanana, Lockias (2016)
Midlands State University (MSU) has witnessed an about turn in lecturers’ perceptions and beliefs about technology from being negative to positive enthusiastic users of technology. Using the case of MSU this paper reports interplay of factors that have resulted in lecturers’ buy-in in the use of e-learning as a mode of instructional delivery. The study employed Actor Network Theory (ANT) as both a methodological and analytical framework to trace the trajectory of the e-learning programme at MSU. The conspicuous actors were followed using questionnaires, participant observation, and document analysis as well as tracing actors through the trails they left on the e-learning platform. The results show that there are heterogeneous actants which have exerted their agencies on lecturers through multiple associations they created during the implementation of the e-learning programme which has resulted in the lecturers’ change in perception from being techno-phobic to become technology savvies. This article contributes to the growing body of literature that uses ANT to understand e-learning as a socio-technical process. ANT’s contribution to explaining the change in lecturer’s perception is its symmetrical power that can be used to consider technological developments and the human capacity development as equal actants that can exert similar levels of influence on each other to bring about the required change.